Retirement Income Sufficiency: A Comparison Study in Australia and New Zealand - Xiaobo Xu; Martin R. Young; Liping Zou; Jiali Fang (Journal of Risk and Financial Management, 2023)
We use the 2018 survey data from the Household, Income, and Labour Dynamic (HILDA) in Australia and the Household Economic Survey (HES) in New Zealand to investigate the retirement income sufficiency in Australia and New Zealand. Our baseline results indicate that the annuitized net wealth is greater for Australian retirees than for New Zealand retirees. However, New Zealand retirees enjoy a higher level of life satisfaction than Australian retirees. Further analysis reveals a significant greater pre- and postretirement income for the top 10% of wealthy Australian retirees, mainly due to the higher level of homeownership in Australia within this group. Our study fills the gap in the existing literature, which studies the macro- and microlevel influences on Australia and New Zealand retirees, and it also offers important policy implications.
Keywords: D14; D31; G51; I31; J14; J17; J26; 650; Australia; Blinder-Oaxaca decomposition; demographic traits; government pension system; income sufficiency; individual financial positions; New Zealand; retiree; retirement planning